Dynamic performance modelling of tidal stream turbines in ocean waves. - James A. C Orme (2006)
The primary aim of this work is to develop a tool to predict the lifetime performance of a tidal stream turbine. This involves the experimental validation of Blade Element Momentum Theory (BEMT) and implementation of an extended model to optimise blade design and predict performance over the operating range. Time varying non-linear upstream flows, such as wave action and velocity gradients are considered and the model is extended into the time domain to obtain the dynamic response of the rotor. In addition, to rationalise the environmental conditions that a device will encounter in its lifetime, representative sea-states and occurrences must be defined. A 1m diameter turbine is tow tested in the River Tawe. It is monitored and controlled such that the performance can be analysed over the operating range. An automated electrical control system is also tested. The results are compared to BEMT. The BEMT is numerically implemented and examined to determine its limitations. Off-optimum performance is considered. The model is extended to incorporate a time dependent flow field with additional velocity and acceleration terms to allow the consideration of wave kinematics. Resultant forces are defined and calculated for particular environmental conditions. Finally the results are interpreted to allow the estimation of lifetime loadings including peak loads and fatigue. The model is validated and a good correlation is found relative to standard BEMT. It is concluded that both a velocity gradient and a wave action may significantly reduce power output whilst increasing the loads on a system. It is also concluded that a 3 bladed rotor encounters far lower loadings than a 2 bladed equivalent over the device lifetime. It is also the intention of this study to compare and contrast various tidal stream turbine support structure concepts in terms of the suitability of each to withstand the lifetime loadings at reasonable cost. A number of support structure concepts are investigated from an impartial perspective. In conclusion there is not one concept which clearly surpasses the others in all areas.